2019
DOI: 10.18178/ijtef.2019.10.1.632
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tax Planning on Financial Performance in the Stock Exchange of Thailand

Abstract: This paper aims to examine the association of tax planning (hereafter called TP) on financial performance (hereafter called FP) in the Stock Exchange of Thailand during the year 2014-2016. The sample size, which excludes the financial sector, consists of 873 firm-years. The TP is measured by effective tax rate (hereafter called ETR) and the ratio of tax expenses to total assets (hereafter called TAX/ASSET), while the FP is measured by return on equity. This paper finds that the TP has both effects on the FP. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
7
0
1
Order By: Relevance
“…Based on these results, hypothesis 1 is accepted, meaning that tax compliance has an influence on the company's financial performance. With a negative coefficient, this study shows that tax compliance decreases the company's financial performance, this result is in accordance with previous research (De Schoenmaker et al, 2014;Thanjunpong & Awirothananon, 2019). These results indicate that some companies do not utilize industrial facilities provided by the government to compliant taxpayers, such as restitution and import facilities.…”
Section: Regression Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Based on these results, hypothesis 1 is accepted, meaning that tax compliance has an influence on the company's financial performance. With a negative coefficient, this study shows that tax compliance decreases the company's financial performance, this result is in accordance with previous research (De Schoenmaker et al, 2014;Thanjunpong & Awirothananon, 2019). These results indicate that some companies do not utilize industrial facilities provided by the government to compliant taxpayers, such as restitution and import facilities.…”
Section: Regression Resultssupporting
confidence: 91%
“…In addition, there are other facilities that help smooth the business of the company (Chude & Chude, 2015;Matarirano et al, 2019), such as restitution facilities and goods import facilities provided by the Indonesian government for compliant taxpayers to help improve financial performance. Even so, several other studies found a negative effect of tax on financial performance (De Schoenmaker et al, 2014;Thanjunpong & Awirothananon, 2019). Therefore, taxes are part of the company's profit and loss which has an impact on financial performance.…”
Section: Tax Compliance On Financial Performancementioning
confidence: 99%
See 1 more Smart Citation
“…the findings of Kawor, & Kportorgbi, (2014);Thanjunpong, & Awirothananon, (2019) and contradict with that of Ogundajo, & Onakoya, (2016). Based on these, the null hypothesis one is rejected to signify the significant positive effect of GAAPETR on financial performance of listed industrial goods firms in Nigeria.…”
Section: Table 5: Random-effects Gls Regressionmentioning
confidence: 56%
“…On the other hand, CASHETR has a negative significance effect on financial performance of listed industrial goods firms in Nigeria represented by ROA. This implies that the more firms increase their tax planning activities through CASHETR the lower their financial performance in terms of ROA this is in line with the findings of Kawor, & Kportorgbi, (2014); Thanjunpong, & Awirothananon, (2019) and contradict with that of Ogundajo, & Onakoya, (2016). Based on these findings, Hypothesis two is also rejected to imply that CASHETR has a significant negative effect on financial performance of listed industrial goods firms in Nigeria.…”
Section: Table 5: Random-effects Gls Regressionmentioning
confidence: 62%